Crosstalk between oligodendrocytes and cerebral endothelium contributes to vascular remodeling after white matter injury - Pham, Loc-Duyen D. (2012)
After stroke and brain injury, cortical gray matter recovery involves mechanisms of neurovascular matrix remodeling. In white matter however, the mechanisms of recovery remain unclear. In this present study, we demonstrate that oligodendrocytes secrete matrix metalloproteinase-9 (MMP-9), which accelerates the angiogenic response after white matter injury. In primary oligodendrocyte cultures, treatment with the pro-inflammatory cytokine interleukin-1β (IL-1β) induced an upregulation and secretion of MMP-9. Conditioned media from IL-1β-stimulated oligodendrocytes significantly amplified matrigel tube formation in brain endothelial cells, indicating that MMP-9 from oligodendrocytes can promote angiogenesis in vitro. Next we asked whether similar signals and substrates operate after white matter injury in vivo. Focal white matter injury and demyelination was induced in mice via stereotactic injection of lysophosphatidylcholine (LPC) into corpus callosum. Western blot analysis showed that IL-1β expression was increased in damaged white matter. Immunostaining demonstrated MMP-9 signals in MOBP (myelin-associated oligodendrocytic basic protein)-positive oligodendrocytes. Treatment with an IL-1β-neutralizing antibody suppressed the MMP-9 response in oligodendrocytes. Finally, we confirmed that the broad spectrum MMP inhibitor GM6001 inhibited angiogenesis around the injury area in this white matter injury model. In gray matter, a neurovascular niche promotes cortical recovery after brain injury. Our study suggests that an analogous oligovascular niche may mediate recovery in white matter.